2014
DOI: 10.1007/s00415-014-7564-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the course of functional status of patients with ALS: a systematic review

Abstract: The progressive course of amyotrophic lateral sclerosis (ALS) results in an ever-changing spectrum of the care needs of patients with ALS. Knowledge of prognostic factors for the functional course of ALS may enhance clinical prediction and improve the timing of appropriate interventions. Our objective was to systematically review the evidence regarding prognostic factors for the rate of functional decline of patients with ALS, assessed with versions of the ALS Functional Rating Scale (ALSFRS). Two reviewers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 46 publications
5
36
0
3
Order By: Relevance
“…For example, score 0 or 1 at item 12 (respiratory insufficiency) of the ALSFRS-R has a different meaning in terms of survival than a score 0 or 1 at item 9 (climbing stairs). This may as well explain the results of a recent systematic review in which authors found in general low levels of evidence for several prognostic factors, often used by professionals in individual prognostication, examined on a selection of 13 papers dealing with ALS prognosis [14]. Although the ALSFRS-R score has been shown to be significantly associated with survival [13,15,18,19], few studies considered factors influencing ALS decline and survival and our study shows that they might differ.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, score 0 or 1 at item 12 (respiratory insufficiency) of the ALSFRS-R has a different meaning in terms of survival than a score 0 or 1 at item 9 (climbing stairs). This may as well explain the results of a recent systematic review in which authors found in general low levels of evidence for several prognostic factors, often used by professionals in individual prognostication, examined on a selection of 13 papers dealing with ALS prognosis [14]. Although the ALSFRS-R score has been shown to be significantly associated with survival [13,15,18,19], few studies considered factors influencing ALS decline and survival and our study shows that they might differ.…”
Section: Discussionmentioning
confidence: 64%
“…Studies on prognostic factors on functional decline and survival may enhance clinical decision making, patient counselling and treatment selection [14].…”
Section: Discussionmentioning
confidence: 99%
“…Median survival of ALS patients is 3 years after symptom onset and the main cause of death is respiratory failure. The disease course is negatively influenced by older age at onset, early respiratory dysfunction, bulbar onset, a short time to diagnosis and the presence of a C9orf72 repeat expansion [6, 11, 12, 15, 34]. Previous studies suggested a negative effect of executive dysfunction or neurobehavioral changes on survival of ALS patients, although the use of general measures for behavioral changes precluded firm conclusions in some of them [10, 15, 18, 23, 26].…”
Section: Introductionmentioning
confidence: 99%
“…This latter aspect has an enormous importance in a disease that substantially lacks medical treatment (Beghi et al, 2011) and reliable physical prognostic factors (Creemers et al, 2014). …”
Section: Introductionmentioning
confidence: 99%